Perencanaan Kebutuhan Ruang Terbuka Hijau (RTH) di Kota Kendari: (Studi Kasus: Jalan MT. Haryono, Kota Kendari, Sulawesi Tenggara) - Almajid, Almajid; Ndibale, Wa; Assiddieq, Moch. (Universitas Muhammadiyah Kendari, 2024)
This research examines Green Open Space (RTH), which is one of the facilities that should be provided in an area. The problem in this research is green open space on the MT road. Haryono, which is not well maintained, disrupts the environmental aesthetics of the area. Apart from that, the function of green open spaces that are not optimal has the potential to have an impact on other environmental problems. The aim of the research is to design a green open space plan that is feasible and supports environmental aesthetics in the MT road area. Haryono. The methods used in this research are quantitative and qualitative methods. The choice of this method is seen from the calculation of the planned green open space requirements which will then be explained qualitatively. The research results show that the area of ​​the MT road. Haryono 174,247.93 m2 or equivalent to 17.42 Ha. As is the case, 30% of the need for green open space is on the MT road. Haryono is an area of ​​52,274.39 m2 or the equivalent of 5.23 Ha. So the planned green open space area is 817.39 m2 or the equivalent of 0.08 Ha. The implication of this research is the concept of green open space planning on MT roads. Haryono is planning a green open space with an ecological pattern.